The Sandman. Vol. 8, World's end - Gaiman, Neil (Gaiman, Neil. Sandman library, 1994)
Stephen King's Introduction sets the stage for a series of tales with a haunting geometry--some angular, some parallel, some concentric. An eerie mirror of Chaucer's Canterbury Tales, this collection tells of a group of travelers from throughout time, myth and dream, who converge at a mysterious inn to seek refuge from a "reality storm". Graphic novel format. Mature readers.